2000
DOI: 10.1046/j.1460-2687.2000.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering tennis - slowing the game down

Abstract: Analysis of results from the four major tennis tournaments shows that the percentage of tie breaks in the men’s game has been increasing over the last 30 years. It is hypothesised that this is due to the increasing speed of the serve in the game. There was found to be a significant difference in tie breaks between slower clay surfaces and faster grass surfaces. The women’s game, on the other hand, showed no increase in tie‐breaks and no difference in the number of tie‐breaks between court surfaces. A larger te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 12 publications
1
53
2
1
Order By: Relevance
“…on performance indicators should not be underestimated. The current research shows that the duration of a tennis match is related to the surface speed and the type of ball (Hughes & Clarke, 1995;Haake & Coe, 2000;Unierzyski & Wieczorek, 2004;Miller, 2006;Gillet & Leroy, 2009;Takahashi, et al, 2009) , a player's ranking, tactics, game style (Verlinden, et al 2004;Gillet & Leroy, 2009;Reid, et al, 2010) , and the opponent's characteristics. The association between the player and the opponent is important but, to the knowledge of the authors, no study has analysed interdependence between observed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…on performance indicators should not be underestimated. The current research shows that the duration of a tennis match is related to the surface speed and the type of ball (Hughes & Clarke, 1995;Haake & Coe, 2000;Unierzyski & Wieczorek, 2004;Miller, 2006;Gillet & Leroy, 2009;Takahashi, et al, 2009) , a player's ranking, tactics, game style (Verlinden, et al 2004;Gillet & Leroy, 2009;Reid, et al, 2010) , and the opponent's characteristics. The association between the player and the opponent is important but, to the knowledge of the authors, no study has analysed interdependence between observed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The initial measurements gave a C D of approximately 0.52 for a standard tennis ball and it was found to be independent of Re over the range, 200 000oReo270 000. Chadwick and Haake [16] and Haake et al [9] reported that C D ffi0.55 over the same Re range for a standard tennis ball, a pressureless ball and a larger ball. The difference between the two reported C D levels is attributed to the technique used to measure the ball diameter [5].…”
Section: Effects Of Fuzzmentioning
confidence: 94%
“…Chadwick and Haake [15] used an outer (projected) diameter, which included the nap or fuzz height. Their results also showed that the tennis ball C D could be increased (by raising the fuzz) or decreased (by shaving off the fuzz) by up to 10% [9,15,16].…”
Section: Effects Of Fuzzmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies on ball aerodynamics include that by Bearman and Harvey [3] who found that dimples on a golf ball serve to reduce the critical Reynolds number indicating that surface geometry can have a significant effect on ball flight. Studies related to other sports including cricket [1], tennis [4], baseball [5], volleyball [6] have measured the drag and Magnus forces experienced by a ball during flight for varying velocity and spin conditions and examined the effect on transition and boundary layer separation. This work built on ground-breaking research by Achenbach [7,8] on the aerodynamics of smooth and rough spheres, which showed that increased surface roughness encourages transition to occur at low values of Reynolds number.…”
Section: Introductionmentioning
confidence: 99%